Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1016/j.taap.2013.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific differences in hyperoxic lung injury in mice: Implications for acute and chronic lung disease in humans

Abstract: Sex-specific differences in pulmonary morbidity in humans are well documented. Hyperoxia contributes to lung injury in experimental animals and humans. The mechanisms responsible for sex differences in the susceptibility towards hyperoxic lung injury remain largely unknown. In this investigation, we tested the hypothesis that mice will display sex-specific differences in hyperoxic lung injury. Eight week-old male and female mice (C57BL/6J) were exposed to 72 h of hyperoxia (FiO2>0.95). After exposure to hypero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 44 publications
4
35
1
Order By: Relevance
“…We exposed mice to 90% O 2 to induce hyperoxia, whereas Zhang et al exposed mice to 100% O 2 . The survival time during hyperoxia reported here is longer than that reported by Zhang et al Furthermore, Lingappan et al (35) reported that male mice are more susceptible than female mice to HALI, suggesting genderspecific differences in responses of mice with HALI. Moreover, the responses to hyperoxia and subsequent HALI are influenced by the ambient housing temperature (2).…”
Section: Discussioncontrasting
confidence: 60%
“…We exposed mice to 90% O 2 to induce hyperoxia, whereas Zhang et al exposed mice to 100% O 2 . The survival time during hyperoxia reported here is longer than that reported by Zhang et al Furthermore, Lingappan et al (35) reported that male mice are more susceptible than female mice to HALI, suggesting genderspecific differences in responses of mice with HALI. Moreover, the responses to hyperoxia and subsequent HALI are influenced by the ambient housing temperature (2).…”
Section: Discussioncontrasting
confidence: 60%
“…While it is possible that sex-specific regulation of TRPA1 expression is responsible for the observed difference, other sexually dimorphic mechanisms may play a role such as the differential production of antioxidant defense systems, protective enzymes, cytokines and other mediators. Increased male susceptibility has been reported for other types of lung injury, including hypoxic lung injury where female mice of the same strain (C57BL/6) displayed higher recovery rates (Lingappan et al, 2013). Differences in acrolein-induced mortality also exist between inbred mouse strains, however, the Trpa1 gene was absent in the list of polymorphic genes linked to strain-specific acrolein susceptibility (Leikauf et al, 2011).…”
Section: Mechanisms Of Trpa1-mediated Toxicological Injuries By Acmentioning
confidence: 93%
“…Resistance to hyperoxia is found to be female predominant in adult animals [19], We found that hyperoxia induced significant sex-related changes in liver oxidative/antioxidative status which were reflected in higher mortality rate of adult male mice [13], and also found that treatment of male mice with E2 could efficiently boost antioxidative system in the liver [14]. In this study…”
Section: Discussionmentioning
confidence: 59%